THE INFLUENCE OF SOCIAL MEDIA MARKETING ON BRAND EQUITY, BRAND TRUST AND BRAND LOYALTY ON TRAVELOKA INSTAGRAM - Tarisa, Tarisa; Giri , Refi Rifaldi Windya (Universitas Islam Lamongan, 2024)
This research is entitled